Placement of Percutaneous Screw through pedicle of fractured Vertebrae in fixation of Thoracolumbar spinal fractures - an observational analysis - Mehmood, Khalid; Shah, Irfanullah; Aslam, Muhammad; Halawani, Mohammed M (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the safety and effectiveness of percutaneous pedicle screw placement at the level of fractured vertebrae in the treatment of thoracolumbar spinal fractures. Methods: The experiment enrolled 40 participants in stages. Percutaneous pedicle screw fixation classified patients into two groups: those who had a fractured vertebra insertion of pedicle screw (fractured group) and those who did not (the "unfractured group") (control group). The duration of the surgery and the volume of blood loss were both documented. In clinical study, both the ODI and the visual analogue scale were utilized (VAS). Cobb angle, vertebral body index (VBI), and anterior vertebral body height were used for radiographic follow-up (CA). Results: The two groups did not differ significantly in terms of operation time and intraoperative blood loss. VAS and ODI scores remained stable across all follow-up periods. In comparison to the control group, the fragmented group exhibited a higher rate of rectification and a lower rate of AVBH and VBI loss. There was no significant difference between the two groups in terms of CA correction and correction loss following surgery. Conclusion: If a patient suffers a type A fracture of the thoracolumbar spine, percutaneous screw fixation combined with intermediate screws may be beneficial in assisting the patient in healing and preserving their vertebral height.